Review of the leafhopper tribe Macrostelini Kirkaldy (Cicadellidae: Deltocephalinae) in Pakistan with description of a new species - Naveed, Hassan; Zhang, Yalin (Zootaxa, 2018)
The leafhopper tribe Macrostelini is reviewed for Pakistan with description of a new species Macrosteles parafalcatus sp. nov. and a new record Balclutha pararubrostriata n. rec. to Pakistan described and illustrated. Keys are given to distinguish the macrosteline genera and species recorded from Pakistan.